2005
DOI: 10.1088/1009-9271/5/s1/80
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Spectral Characteristics of Thermal and Non-Thermal Emission from Three Black Holes

Abstract: Cygnus X-1 and the gamma-ray transients GRO J0422+32 and GRO J1719 − 24 displayed similar spectral properties when they underwent transitions between the high and low gamma-ray (30 keV to few MeV) intensity states. When these sources were in the high γ-ray intensity state (γ 2 , for Cygnus X-1), their spectra featured two components: a Comptonized shape below 200-300 keV with a soft power-law tail (photon index >3) that extended to ∼1 MeV or beyond. When the sources were in the low-intensity state (γ 0 , for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…However, unlike CT95 cases, where there was only one so-called 'pivoting' point at around a few keV, here we have an extra 'pivoting' point at a few hundred keV because of the inclusion of the synchrotron radiation. This is what is observed in black hole candidates (McConnell et al 2000(McConnell et al , 2002Ling and Wheaton 2005b;Mandal and Chakrabarti 2007).…”
Section: Resultssupporting
confidence: 80%
“…However, unlike CT95 cases, where there was only one so-called 'pivoting' point at around a few keV, here we have an extra 'pivoting' point at a few hundred keV because of the inclusion of the synchrotron radiation. This is what is observed in black hole candidates (McConnell et al 2000(McConnell et al , 2002Ling and Wheaton 2005b;Mandal and Chakrabarti 2007).…”
Section: Resultssupporting
confidence: 80%
“…In the present case, however, the high energy photons are produced due to Comptonization of the non-thermal photons. We have been able to fit high energy data of several black hole candidates which were presented in Ling and Wheaton (2003, 2005a, 2005b. Details will be presented elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed to emit significant emission above 100 keV including a power law tail extending out to greater than 2005b). Based on BATSE occultation analysis, Ling & Wheaton (2005b) have shown that in the high gamma-ray intensity (hard) state, the spectrum consists of a Comptonized shape below 200-300 keV with a soft (Γ > 3) power-law tail extending to at least 1 MeV. In the low-intensity (soft) state, however, the spectrum takes on a different shape: In this case, the entire spectrum from 30 keV to 1 MeV is characterized by a single power law with a harder index Γ ∼ 2 − 2.7.…”
Section: Cyg X-1mentioning
confidence: 99%